THE IMPLEMENTATION OF MAKE A MATCH TECHNIQUE TO INCREASE STUDENTS’ VOCABULARY MASTERY (A Classroom Action Research at Fourth Grade of SDN 4 Troso in Academic Year 2017/2018) - Nurul Azizah Fitriana (Universitas Islam Nahdlatul Ulama Jepara, 2018)
This research is aimed to find out: (1) The students’ problem in learning Vocabulary and (2) The extend the use of Make a Match technique to increase students’ vocabulary mastery for the fourth grade students of SDN 4 Troso in the academic 2017/2018. The method in this research is Classroom Action Research. It was carried out in three cycles of actions. In each cycle consist of Planning, Action, Observation, and Action. The Research was done based on Kemmis and Mac Taggart Design. The technique for collecting data are observation, test, and interview. The data were analyzed by using quantitative data and qualitative data.The problem got in this research was the students feel tired and bored, because the teacher asked the students to write the vocabularies and to pronounce the vocabularies. After conducted of Make a Match Technique students enthusiastic in the lesson and looked enjoy during the implementation of Make a Match Technique . The result of this research showed that Make a Match Technique can improve students' vocabulary. It could be seen from the average in every cycle.The first cycle was 70.98, then the second cycle was 73.7, and the third cycle was 76.1, which stated that Make a Match Technique was effective to taught vocabulary mastery at Fourth Grade of SD Negeri 4 Troso.